2020
DOI: 10.1055/s-0040-1713175
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Fondaparinux in Autoimmune Heparin-Induced Thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is an immune adverse reaction to heparin that is associated with life-threatening thrombotic complications. More rarely, HIT may begin after stopping of heparin or after flushes of heparin (autoimmune HIT). Fondaparinux has been proposed as a candidate treatment for HIT, but there are few data on its use in autoimmune HIT. An 86-year-old man with a history of diabetes mellitus, arterial hypertension, and hypercholesterolemia was admitted to our hospital for carotid endart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Notably, our present patient demonstrated progression of her thrombotic burden in the setting of fondaparinux. Three prior case reports have similarly demonstrated fondaparinux failure in patients with HITT, with in vitro documentation in two of these cases showing cross‐reactivity based on the augmentation of platelet activation with fondaparinux 6–8 . We did not check for in vitro cross‐reactivity of fondaparinux, but it is possible that in a subset of patients with HITT, fondaparinux may augment platelet activation with antibodies that cross‐react with PF4/fondaparinux complexes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Notably, our present patient demonstrated progression of her thrombotic burden in the setting of fondaparinux. Three prior case reports have similarly demonstrated fondaparinux failure in patients with HITT, with in vitro documentation in two of these cases showing cross‐reactivity based on the augmentation of platelet activation with fondaparinux 6–8 . We did not check for in vitro cross‐reactivity of fondaparinux, but it is possible that in a subset of patients with HITT, fondaparinux may augment platelet activation with antibodies that cross‐react with PF4/fondaparinux complexes.…”
Section: Discussionmentioning
confidence: 97%
“…Three prior case reports have similarly demonstrated fondaparinux failure in patients with HITT, with in vitro documentation in two of these cases showing cross-reactivity based on the augmentation of platelet activation with fondaparinux. [6][7][8] We did not check for in vitro cross-reactivity of fondaparinux, but it is possible that in a subset of patients with HITT, fondaparinux may augment platelet activation with antibodies that cross-react with PF4/fondaparinux complexes. While these reports remain anecdotal, our present case adds to the growing evidence of fondaparinux's failure in some HITT cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pistulli and colleagues [163] reported a patient who developed HIT with UFH and LMWH in whom the platelet count continued to decline after switching to therapeutic-dose fondaparinux; these authors found laboratory evidence of increased platelet activation in the presence of fondaparinux. Sartori and Cosmi [164] also reported a case of aHIT following a single dose of UFH that was also associated with clinical evidence of fondaparinux failure (persisting thrombocytopenia, new venous thrombosis), although in vitro studies to document cross-reactivity were not performed.…”
Section: Fondaparinux As a Treatment Of Hitmentioning
confidence: 99%
“…In recent years, there has been increasing use of the term autoimmune heparin-induced thrombocytopenia (aHIT) to describe patients whose blood samples activate platelets in the absence of exogenous heparin (ie, in the no-heparin/buffer-control serotonin release assay [SRA]). 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 This term has been proposed to include not only syndromes in which patients develop anti–PF4-mediated thrombotic thrombocytopenia without proximate heparin exposure, such as spontaneous HIT and vaccine-induced immune thrombotic thrombocytopenia, but also several clinically severe HIT subtypes that occur after heparin exposure. These additional entities include delayed-onset HIT, persistent HIT, heparin flush–induced HIT, and severe HIT with a platelet count <20 000/μL with associated disseminated intravascular coagulation.…”
mentioning
confidence: 99%